Raman spectra of micellar casein powders prepared with wet blending of glycomacropeptide and micellar casein concentrate. (26th December 2022) - Panthi, Ram R; Shibu, Sini N; Ochalski, Tomasz J; O'Mahony, James A
Abstract : Understanding the molecular properties and interactions of components within high‐protein dairy powders is important in predicting rehydration performance. Raman spectroscopy was used to generate molecular information which provided insights into interactions between caseins in micellar casein concentrate (MCC) powder formulated with varying proportions of glycomacropeptide (GMP). The Raman bands showed intense peaks at 1446 to 1476 cm −1 (due to CH2 vibration) and 1653 to 1668 cm −1 (due to C=O of Amide I and C=C bond) in MCC powder samples blended with GMP. Enhanced rehydration characteristics of MCC powder containing GMP matched with these differences in Raman peak intensity. Abstract : Raman spectroscopy coupled with multivariate data analysis facilitate understanding the molecular properties of micellar casein concentrate (MCC) powder blended with glycomacropeptide (GMP).